Evaluation of the logistics center locations using a multi-criteria spatial approach - Önden, Ismail; Acar, Avni Zafer; Eldemir, Fahrettin (Transport, 2018)
The private sector assumes that logistics centers create cost benefits for their operations. On the other hand, the public sector also assumes that logistics sectors maintain harmony with an aim to improve the logistics network structure and efficiency. In Turkey, nineteen logistics centers are on-going to develop a system approach and integrate different transportation modes to increase logistics performance. In this study, we focused on a multi-stage methodology that combines the fuzzy analytic hierarchy process, spatial statistics and analysis approaches to evaluate the suitability degrees of the logistics centers in the study area. To reach the suitability levels, seven decision criteria were considered alongside their priority levels. These criteria were proximities to highway, railway, airports, and seaports; volume of international trade; total population; and handling capabilities of the ports. The reached suitability degrees were tested using a sensitivity analysis. Different scenarios were discussed to understand how the decision environment might illustrate differences in spatial aspect. First published online 25 May 2016